Fluctuating Carbonaceous Networks with a Persistent Molecular Shape: A Saddle‐Shaped Geodesic Framework of 1, 3, 5‐Trisubstituted Benzene (Phenine). (6th June 2018) - Ikemoto, Koki; Lin, Jennie; Kobayashi, Ryo; Sato, Sota; Isobe, Hiroyuki
Abstract: A saddle‐shaped macromolecule has been synthesized. The molecule was designed as a geodesic saddle with 1, 3, 5‐trisubstituted benzene (named phenine) as the fundamental unit. The phenines were woven into a polygonal framework that was composed of 168 sp 2 ‐hybridized carbon atoms. The saddle‐shaped structure with unique symmetry showed atypical conformational changes. The biaryl linkages in this molecule had a small energy barrier for rotation, and these structural fluctuations resulted in seven 1 H NMR resonances representing 84 aromatic hydrogen atoms. Nevertheless, the overall saddle shape of the molecule was persistent, and the "up" and "down" orientations of phenine moieties circulated to give average 1 H resonances. The structural characteristics of this molecule, including the anomalous entropy‐driven dimerization, may deepen our understanding of defect‐rich graphitic sheets. Abstract : Sattelfest : Planar‐trigonales 1, 3, 5‐trisubstituiertes Benzol wurde zu einer isoretikulären geodätischen Gerüststruktur synthetisch verwoben. Das resultierende sattelförmige Molekül hat eine einzigartige fluktuierende Struktur aufgrund der kleinen Energiebarriere der Rotation um die Biarylbindungen (siehe Bild). Die Sattelform des Moleküls im Ganzen wird dabei jedoch beibehalten.